Evaluation of Jurists and Police officers Views About Judicial Process and Laws Related with Rape Cases - Gölge, Zeynep Belma; Yavuz, Mehmet Fatih; Başkan, Tanıl Mehmet (The Bulletin of Legal Medicine, 2000)
Taking into consideration of its juridical, medical, psychological and social aspects, rape is the most serious offence against the human body following homicide.. Out of 400, exactly 355 professionals for a response rate of 88.75 % participated in this research by completing a questionnaire containing statements about the trial by 3 factors " punishment" "victim’s influence on trial" and "prosecution". 100 lawyers, who are enrolled in the " İstanbul Bar Association" as a research group, 80 judges-attorneys and 75 judge-attorney trainees, who are taking office in the court system in İzmir and Ankara and 100 police officers, who are taking office in İstanbul were the participants. The aim of this study is to scan the perspectives of these professionals about the penalty system regarding rape cases. More than half of the participants think that manners or appearance of the rape victim, influences the trial and the victim’s testimony is not succesful. The police officers, compared to others, do believe that the penalty has to be more serious. %57 of the lawyers, %32 of the judges-attorneys, %68 of the judge-attorney trainees and %6l of the police officers agree that the laws regulating sexual assault offences is too tolerant and only a small part of them agree that the judges are tolerant to rapists.Key Words: : Rape, judgment, police officer, jurist
Keywords: rape; judgment; police officer; jurist